(untitled) (Perner’s Contacts, 2013)
Presented paper is devoted to simulation of temporarily single-track tram line traffic in Ostrava - Svinov. Simulation model was created using software Witness 2008. In order to create and validate the simulation model traffic survey was done. After validating the model a simulation experiment was executed. Within the experiment the impact of proposed traffic control logic on delay and queue length was examined.